1999
DOI: 10.1086/307944
|View full text |Cite
|
Sign up to set email alerts
|

Determining the Physical Properties of the B Stars. I. Methodology and First Results

Abstract: We describe a new approach to Ðtting the UV-to-optical spectra of B stars to model atmospheres and present initial results. Using a sample of lightly reddened stars, we demonstrate that the Kurucz model atmospheres can produce excellent Ðts to either combined low-dispersion IUE and optical photometry or HST FOS spectrophotometry, as long as the following conditions are fulÐlled : (1) an extended grid of Kurucz models is employed ; (2) the IUE NEWSIPS data are placed on the FOS absolute Ñux system using the Mas… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
77
1

Year Published

2001
2001
2016
2016

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 69 publications
(85 citation statements)
references
References 37 publications
7
77
1
Order By: Relevance
“…For each star, the T eff and log(g) adopted by W&H were used, and each model photosphere was represented by an Kurucz LTE model atmosphere. Direct comparison to non-LTE model atmospheres (Grigsby 1991;Grigsby et al 1992) and to observed UV-to-optical spectral energy distributions (Fitzpatrick & Massa 1999) demonstrates that the approximation of LTE model atmospheres is a reasonable one for this range of stellar parameters.…”
Section: Calculationsmentioning
confidence: 94%
“…For each star, the T eff and log(g) adopted by W&H were used, and each model photosphere was represented by an Kurucz LTE model atmosphere. Direct comparison to non-LTE model atmospheres (Grigsby 1991;Grigsby et al 1992) and to observed UV-to-optical spectral energy distributions (Fitzpatrick & Massa 1999) demonstrates that the approximation of LTE model atmospheres is a reasonable one for this range of stellar parameters.…”
Section: Calculationsmentioning
confidence: 94%
“…After applying these criteria, we are left with a catalog of 332,037 sources consisting of 123,567 stars (37%) and 208,470 galaxies (63%), 195,426 (59%) of which satisfy Equation (18). We then correct for Galactic dust extinction using the Schlegel et al (1998) dust map and the extinction curve of Fitzpatrick & Massa (1999). Source-count histograms of the K s magnitudes for stars and the corrected K s magnitudes for galaxies are shown by the solid black and dashed blue lines, respectively, in Figure 6.…”
Section: Photometric Fittingmentioning
confidence: 99%
“…10 For the optical and NIR filters we used the extinction coefficients from De . For the F275W and F336W filters we followed the prescription of De , adding 1.5 to the Fitzpatrick & Massa (1999) massive stars has always been hampered by their rarity, due to the short timescales involved in their evolution and the steepness of the IMF. On the theoretical side, models of massive stars are still affected by major uncertainties.…”
Section: Stellar Clocks: Ms Turn-off and Pms Turn-onmentioning
confidence: 99%